LIQUEFACTION OF TURKISH LIGNITES AND ASPHALTITES WITH A TURKISH VACUUM RESIDUAL OIL - BOLAT, E; KAVLAK, C; YAHN, G; DINCER, S (ELSEVIER SCIENCE BV, 1992)
Liquefaction studies in a magnetically stirred autoclave were carried out using different types of lignite and asphaltite. Tupras vacuum residue oil was coprocessed with Beysehir, Cayirhan, Goynuk, Keles and Orhaneli lignites, and Silopi and Sirnak asphaltites. Coprocessing was performed under liquefaction conditions of 2:1 solvent: lignite or asphaltite ratio, 440-degrees-C, 80 atm hydrogen pressure for 1 hour reaction time. Total conversions ranging from 40.3 to 92.1% (d.a.f.) for both lignites and asphaltites were obtained. A comparison of liquefaction yields obtained in vacuum residue oil with those obtained using tetralin or anthracene and creosote oils as solvent, under the same operation conditions, was made.
Keywords: PETROLEUM DERIVED SOLVENTS; BROWN COAL; HYDROGENATION; Chemistry; Energy & Fuels; Engineering